Effects of harringtonine on peroxidation and dynamic microstructure of membrane lipids of myocardial sarcoplasmic reticulum in rat - Zhu Ming-Yan; Jin Wan-Bao; Zhao Nai-Cai (Acta Pharmacologica Sinica, 2016)
A I M : T o s t u d y t h e d f e c m o f h a r r i n g t o n in e ( H a r ) on pe~xidaifon and dynamic mierostrueture of m ~ l ! b r a ltl e il p i d s a n d th e r e l a t i o n s h i p b e t w e e n ht e m . METHoDS: A nanose~nd time-resolved lfuom. m eter w a8 used to study ht e e fects of I-Iar on dynamic m ierostrueture of sarcoplasmic reticulum (SR)vesicl髑 from ratmyocardium. The~-nount ofilpid pezoxide wa8 measured with thiobarbituric add testand expressed asainountofm alona1.de&ydlc add (MAA ). RESULTS: liar 10 nag ·LI1 i a c c e s s e d M A A i n S R ( fr o m 1 . 7 ± 0 . 8 协 5 . 4 土 5 . 1 ~tmol/gprotein,P